Unique physiological and regulatory activity drives divergent toxin and non-toxin gene expression in rattlesnake accessory venom glands - Claire Kim; Sierra N. Smith; Siddharth S. Gopalan; Samuel R. Kerwin; Kaas Ballard; Blair W. Perry; Cara F. Smith; Anthony J. Saviola; Richard H. Adams; Stephen P. Mackessy; Todd A. Castoe (Toxicon, 2025)

Ranging Behavior of Philippine Tarsiers (Carlito syrichta) Inhabiting a Protected Forest Fragment in Misamis Oriental, Mindanao: Implications for Monitoring Nocturnal Primates - Simeon Gabriel F. Bejar; Danah Marie P. Purificacion; Lemnuel V. Aragones; Marilyn M. Balais; Anna Pauline O. de Guia; Melizar V. Duya; Perry S. Ong; Mariano Roy M. Duya (International Journal of Primatology, 2025)

Water level drawdown and perennial vegetation impact litter decomposition in the sediment of a eutrophic wetland in the Netherlands - Kerstin Bouma; Mats I. Douma; G. F. Veen; Perry Cornelissen; Mennobart R. van Eerden; Elisabeth S. Bakker (Wetlands Ecology and Management, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Sleeping Site Selection, Sleep-related Positional Behavior, and Social System of Philippine Tarsiers (Carlito syrichta) Inhabiting a Protected Forest Fragment in Mindanao Island, Philippines - Simeon Gabriel F. Bejar; Danah Marie P. Purificacion; Lemnuel V. Aragones; Marilyn M. Balais; Anna Pauline O. de Guia; Melizar V. Duya; Perry S. Ong; Mariano Roy M. Duya (International Journal of Primatology, 2024)

Digital strategies for nitrogen management in grain production systems: lessons from multi-method assessment using on-farm experimentation - A. F. Colaço; B. M. Whelan; R. G. V. Bramley; J. Richetti; M. Fajardo; A. C. McCarthy; E. M. Perry; A. Bender; S. Leo; G. J. Fitzgerald; R. A. Lawes (Precision Agriculture, 2024)
During the past few decades, a range of digital strategies for Nitrogen (N) management using various types of input data and recommendation frameworks have been developed. Despite much research, the benefits accrued from such technology have been equivocal. In this work, thirteen methods for mid-season N recommendations in cereal production systems were evaluated simultaneously, ranging from simple mass balance through to non-mechanistic approaches based on machine learning. To achieve this, an extensive field research program was implemented, comprising twenty-one N strip trials implemented in wheat and barley fields across Australia over four cropping seasons. A moving window regression approach was used to generate crop response functions to applied N and calculate economically optimal N rates along the length of the strips. The N recommendations made using various methods were assessed based on the error against the optimal rate and expected profitability. The root mean squared error of the recommendations ranged from 15 to 57 kg/ha. The best performing method was a data-driven empirical strategy in which a multivariate input to characterise field and season conditions was abundantly available and used to predict optimal N rates using machine learning. This was the only approach with potential to substantially outperform the existing farmer management, reducing the recommendation error from 42 to 15 kg/ha and improving profitability by up to A$47/ha. Despite being reliant on extensive historical databases, such a framework shows a promising pathway to drive production systems closer towards season- and site-specific economically optimum recommendations. Automated on-farm experimentation is a key enabler for building the necessary crop response databases to run empirical data-driven decision tools.

Electrocardiogram to Determine Mitral and Aortic Valve Opening and Closure - M. Rifqi Aufan; Zachary T. Jost; Neal J. Miller; Oleg F. Sharifov; Himanshu Gupta; Gilbert J. Perry; J. Michael Wells; Thomas S. Denney; Steven G. Lloyd (Cardiovascular Engineering and Technology, 2023)

Polymorphism of the follicle stimulating hormone receptor does not impact reproductive performance or in-vitro embryo production in beef heifers - Alexandria P. Snider; Hannah K. Yake; Camryn D. Granger; Shelby L. Rosasco; Tara G. McDaneld; Warren M. Snelling; Chad C. Chase; Jeremy R. Miles; Clay A. Lents; Lacey K. Quail; Jerica J.J. Rich; Kaitlin M. Epperson; et al. (Theriogenology, 2023)

A Case Study of Large Floodplain River Restoration: Two Decades of Monitoring the Merwin Preserve and Lessons Learned through Water Level Fluctuations and Uncontrolled Reconnection to a Large River - Levi E. Solomon; Andrew F. Casper; Kristopher A. Maxson; James T. Lamer; Trent W. Ford; K. Douglass Blodgett; Tharran Hobson; Denim Perry; Nathan T. Grider; Rob B. Hilsabeck; Thad R. Cook; Kevin S. Irons; et al. (Wetlands, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Does blood flow limit acute hypoxia performance in larval zebrafish (Danio rerio)? - M. C. Hughes; S. F. Perry (Journal of Comparative Physiology B, 2021)

Limited genetic parallelism underlies recent, repeated incipient speciation in geographically proximate populations of an Arctic fish ( Salvelinus alpinus ) - Sarah J. Salisbury; Gregory R. McCracken; Robert Perry; Donald Keefe; Kara K.S. Layton; Tony Kess; Cameron M. Nugent; Jong S. Leong; Ian R. Bradbury; Ben F. Koop; Moira M. Ferguson; Daniel E. Ruzzante (Molecular Ecology, 2020)
The genetic underpinnings of incipient speciation, including the genomic mechanisms which contribute to morphological and ecological differentiation and reproductive isolation, remain poorly understood. The repeated evolution of consistently, phenotypically distinct morphs of Arctic Charr ( Salvelinus alpinus ) within the Quaternary period offer an ideal model to study the repeatability of evolution at the genomic level. Sympatric morphs of Arctic Charr are found across this species' circumpolar distribution. However, the specific genetic mechanisms driving this morph differentiation are largely unknown despite the cultural and economic importance of the anadromous morph. We used a newly designed 87k SNP chip to investigate the character and consistency of the genomic differences among sympatric morphs within three recently deglaciated and geographically proximate lakes in Labrador, Canada. We found genetically distinct small and large morph Arctic Charr in all three lakes consistent with resident and anadromous morphs, respectively. A degree of reproductive isolation among sympatric morphs is likely given genome‐wide distributions of outlier SNPs and high genome‐wide F ST s. Across all lakes, outlier SNPs were largely nonoverlapping suggesting a lack of genetic parallelism driving morph differentiation. Alternatively, several genes and paralogous copies of the same gene consistently differentiated morphs across multiple lakes suggesting their importance to the manifestation of morphs. Our results confirm the utility of Arctic Charr as a model for investigating the predictability of evolution and support the importance of both genetic parallelism and nonparallelism to the incipient speciation of Arctic Charr morphs.

Living in small spaces: Forest fragment characterization and its use by Philippine tarsiers (Tarsius syrichta Linnaeus, 1758) in Mindanao Island, Philippines - Simeon Gabriel F. Bejar; Mariano Roy M. Duya; Melizar V. Duya; John Michael M. Galindon; Bonifacio O. Pasion; Perry S. Ong (Primates, 2020)

Control history, longitude and multiple abiotic and biotic variables predict the abundances of invasive brushtail possums in New Zealand forests - David M. Forsyth; David S. L. Ramsey; Mike Perry; Meredith McKay; Elaine F. Wright (Biological Invasions, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Exploring fire adaptation in a land with little fire: serotiny in Leptospermum scoparium (Myrtaceae) - Paul F. Battersby; Janet M. Wilmshurst; Timothy J. Curran; Matthew S. McGlone; George L. W. Perry (Journal of Biogeography, 2017)
Aim Immigrant floras often have distinctive traits, well suited to the host region but absent from the autochthonous flora. An example is serotiny in the New Zealand ( NZ ) small tree, Leptospermum scoparium (Myrtaceae) belonging to a strongly fire‐adapted Australian clade. Serotiny in L. scoparium has been attributed either to strong selection by fire since human settlement, or taken as evidence that pre‐human fire in NZ was more important than assumed. By integrating field data, experimental analyses and long‐term fire histories, we sought to explain the spatial pattern of serotiny in L. scoparium in NZ , and evaluate these two explanations. Location New Zealand. Methods We quantified the distribution of serotiny in L. scoparium by analysing 137 populations distributed across NZ (two previous studies and ours), including 31 with Holocene fire histories. We assessed the relationship of serotiny with a suite of fire and climate environmental predictors, and between serotiny and shoot‐level flammability. Results Serotiny was strongly positively associated with latitude (more in the north), lower rainfall and higher temperatures. Serotinous populations were rare at sites with no history of fire. Serotiny was most prevalent in northern wetlands, where fire was recurrent during the Holocene, but was nearly absent from the southwestern Southern Alps. Shoot‐level flammability and serotiny were not correlated. Main conclusions The distribution of serotiny in L. scoparium relates not only to current environments but also to the legacy of regional shifts in vegetation during Quaternary glacial–interglacial cycles. Serotiny was maintained where the landscape experienced sporadic fire, but it is absent from NZ 's southern South Island because the sparse, open vegetation during the glacials did not support fire. Serotinous L. scoparium populations were therefore more common in the northern North Island. Human transformation of the fire regime over the last 750 years has likely favoured the spread of serotinous populations.

Fresh Water Lens Persistence and Root Zone Salinization Hazard Under Temperate Climate - Sija F. Stofberg; Gualbert H. P. Oude Essink; Pieter S. Pauw; Perry G. B. de Louw; Anton Leijnse; Sjoerd E. A. T. M. van der Zee (Water Resources Management, 2017)

Hydrogen sulfide inhibits Na+ uptake in larval zebrafish, Danio rerio - Yusuke Kumai; Cosima S. Porteus; Raymond W. M. Kwong; Steve F. Perry (Pflügers Archiv - European Journal of Physiology, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Identities and distributions of the co-invading ectomycorrhizal fungal symbionts of exotic pines in the Hawaiian Islands - Nicole A. Hynson; Vincent S. F. T. Merckx; Brian A. Perry; Kathleen K. Treseder (Biological Invasions, 2013)

Compensatory regulation of acid–base balance during salinity transfer in rainbow trout (Oncorhynchus mykiss) - K. M. Gilmour; S. F. Perry; A. J. Esbaugh; J. Genz; J. R. Taylor; M. Grosell (Journal of Comparative Physiology B, 2012)

Does the presence of a seawater gill morphology induced by dietary salt loading affect Cl − uptake and acid–base regulation in freshwater rainbow trout Oncorhynchus mykiss - S. F. Perry; L. Rivero‐Lopez (Journal of Fish Biology, 2012)
The goal of this study was to determine the effect of the changes in gill morphology induced by dietary salt feeding on several aspects of gill function in rainbow trout Oncorhynchus mykiss maintained in fresh water with specific emphasis on Cl − uptake ( J IN Cl − ) and acid–base regulation. The addition of 11% NaCl to the diet caused J IN Cl − to be reduced by c. 45% from 214·4 ± 26·7 to 117·3 ± 17·4 µmol kg −1 h −1 (mean ± s.e .). Rates of Cl − efflux ( J OUT Cl − ), net Cl − flux ( J NET Cl − ), J NET Na + and plasma levels of Na + or Cl − were unaffected by salt feeding. On the basis of significant effect of the salt diet on decreasing the maximal uptake rate of Cl − ( J MAX Cl − ), it would appear that internal salt loading caused a decrease in the number of functional ion transport proteins involved in Cl − uptake ( e.g. Cl − –HCO 3 − exchangers) and decreased the transporting capacity of existing proteins. The acid–base regulating capacity of control fish and salt‐loaded fish was assessed by monitoring arterial blood acid–base status [partial pressure of CO 2 ( P CO 2 ), pH and HCO 3 − ] during exposure to external hypercapnia (nominally 7·5 mm Hg). Both groups of fish exhibited typical compensatory responses to sustained hypercapnia consisting of the gradual accumulation of plasma HCO 3 − and thus metabolic restoration within 24 h of the initial respiratory acidosis elicited by hypercapnia. Overall, the results demonstrate that while Cl − uptake capacity is reduced in salt‐fed fish, there is no associated alteration in acid–base regulating capability.

Chronic cocaine exposure induces putamen glutamate and glutamine metabolite abnormalities in squirrel monkeys - Xiaoxu Liu; J. Eric Jensen; Timothy E. Gillis; Chun S. Zuo; Andrew P. Prescot; Melanie Brimson; Kenroy Cayetano; Perry F. Renshaw; Marc J. Kaufman (Psychopharmacology, 2011)

Roles of cortisol and carbonic anhydrase in acid–base compensation in rainbow trout, Oncorhynchus mykiss - K. M. Gilmour; C. L. Collier; C. J. Dey; S. F. Perry (Journal of Comparative Physiology B, 2010)

p75 neurotrophin receptor regulates basal and fluoxetine-stimulated hippocampal neurogenesis - Michael J. Colditz; Vibeke S. Catts; Noura Al-menhali; Geoffrey W. Osborne; Perry F. Bartlett; Elizabeth J. Coulson (Experimental Brain Research, 2010)

Effects of graded levels of exercise on ipsilateral and contralateral post-exercise resting rectus femoris mechanomyography - William P. S. McKay; Perry Jacobson; Philip D. Chilibeck; Brian L. F. Daku (European Journal of Applied Physiology, 2006)

Methods of screening apricot fruit for resistance to brown rot caused by Monilinia spp. - Monika Walter; Gillian F. McLaren; Jenny A. Fraser; Chris M. Frampton; Kirsty S. H. Boyd-Wilson; Joanne H. Perry (Australasian Plant Pathology, 2004)

Alteration of chromosome 9p21 and/or p16 in benign and dysplastic nevi suggests a role in early melanoma progression (United States) - Tina P. Tran; Linda Titus-Ernstoff; Ann E. Perry; Marc S. Ernstoff; Irene F. Newsham (Cancer Causes & Control, 2002)

Intracellular vesicular trafficking in the gill epithelium of urea-excreting fish - P. Laurent; C. M. Wood; Y. Wang; S. F. Perry; K. M. Gilmour; P. Part; C. Chevalier; M. West; P. J. Walsh (Cell and Tissue Research, 2001)

Intracellular ion levels in erythrocytes and hepatocytes isolated from three teleost species - M. Furimsky; S. F. Perry; T. M. Moon (Journal of Fish Biology, 1999)
Intracellular concentrations of Na + and K + were similar (∼75 mmol l −1 ) in rainbow trout Oncorhynchus mykiss hepatocytes directly following isolation by collagenase digestion, but partial recovery occurred over 6 h with K + levels increasing to 110 mmol l −1 and Na + levels decreasing to 42 mmol l −1 . Black bullhead Ameiurus melas hepatocytes exhibited higher intracellular concentrations of K + (90 mmol l −1 ) than Na + (55 mmol l −1 ) with no recovery occurring over 6 h following cell isolation. Concentrations of Na + , K + and Cl − in eel Anguilla rostrata hepatocytes were similar (∼ 55 mmol l −1 ) following isolation, with no recovery occurring over time. Erythrocytes from all species apparently did not experience an intracellular ion imbalance following isolation as indicated by high K + levels ( −1 ) and low Na + levels ( −1 ) during the entire 24‐h monitoring period. Although hepatocytes from all species exhibited an ion imbalance post‐isolation, comparison of their in vitro intracellular Na + and K + concentrations with those in plasma demonstrated that directionally correct ion gradients still exist across the cell membrane, albeit differing from those that would be found in the tissue in vivo .

The influence of chronic anaemia on catecholamine secretion in the rainbow trout ( Oncorhynchus mykiss ) - S. F. Perry; C. J. Montpetit; A. E. Julio; K. Moore (Journal of Comparative Physiology B, 1999)

Cardiovascular control via angiotensin II and circulating catecholamines in the spiny dogfish, Squalus acanthias - N. J. Bernier; K. M. Gilmour; Y. Takei; S. F. Perry (Journal of Comparative Physiology B, 1999)

Short-term treatment with citicoline (CDP-choline) attenuates some measures of craving in cocaine-dependent subjects: a preliminary report - Perry F. Renshaw; Sarah Daniels; Leslie H. Lundahl; Veronica Rogers; S. E. Lukas (Psychopharmacology, 1999)

The effects of arginine vasotocin and catecholamines on nitrogen excretion and the cardio-respiratory physiology of the gulf toadfish, Opsanus beta - S. F. Perry; K. M. Gilmour; C. M. Wood; P. Pärt; P. Laurent; P. J. Walsh (Journal of Comparative Physiology B, 1998)

Population structure of nuclear and mitochondrial DNA variation among humpback whales in the North Pacific - C. S. BAKER; L. MEDRANO‐GONZALEZ; J. CALAMBOKIDIS; A. PERRY; F. PICHLER; H. ROSENBAUM; J. M. STRALEY; J. URBAN‐RAMIREZ; M. YAMAGUCHI; O. VON ZIEGESAR (Molecular Ecology, 1998)
The population structure of variation in a nuclear actin intron and the control region of mitochondrial DNA is described for humpback whales from eight regions in the North Pacific Ocean: central California, Baja Peninsula, nearshore Mexico (Bahia Banderas), offshore Mexico (Socorro Island), southeastern Alaska, central Alaska (Prince Williams Sound), Hawaii and Japan (Ogasawara Islands). Primary mtDNA haplotypes and intron alleles were identified using selected restriction fragment length polymorphisms of target sequences amplified by the polymerase chain reaction (PCR–RFLP). There was little evidence of heterogeneity in the frequencies of mtDNA haplotypes or actin intron alleles due to the year or sex composition of the sample. However, frequencies of four mtDNA haplotypes showed marked regional differences in their distributions (Φ ST = 0.277; P n = 205 individuals) while the two alleles showed significant, but less marked, regional differences (Φ ST = 0.033; P n = 400 chromosomes). An hierarchical analysis of variance in frequencies of haplotypes and alleles supported the grouping of six regions into a central and eastern stock with further partitioning of variance among regions within stocks for haplotypes but not for alleles. Based on available genetic and demographic evidence, the southeastern Alaska and central California feeding grounds were selected for additional analyses of nuclear differentiation using allelic variation at four microsatellite loci. All four loci showed significant differences in allele frequencies (overall F ST = 0.043; P n = 139 chromosomes per locus), indicating at least partial reproductive isolation between the two regions as well as the segregation of mtDNA lineages. Although the two feeding grounds were not panmictic for nuclear or mitochondrial loci, estimates of long‐term migration rates suggested that male‐mediated gene flow was several‐fold greater than female gene flow. These results include and extend the range and sample size of previously published work, providing additional evidence for the significance of genetic management units within oceanic populations of humpback whales.

CDP840 - M. J. Perry; J. O’Connell; C. Walker; T. Crabbe; D. Baldock; A. Russell; S. Lumb; Z. Huang; D. Howat; R. Allen; M. Merriman; J. Walls; et al. (Cell Biochemistry and Biophysics, 1998)

The 10th Conference of the Entomological Society of Israel - Rachel Galun; I. Ishaaya; Sara Yablonski; Zmira Mendelson; Y. Mansour; Svetlana Kontsedalov; U. Pluschkell; A. R. Horowitz; A. R. Horowitz; Sara Yablonski; Zmira Mendelson; I. Ishaaya; et al. (Phytoparasitica, 1997)

Respiratory and acid‐base disturbances in rainbow trout blood during exposure to chloramine‐T under hypoxia and hyperoxia - M. D. Powell; S. F. Perry (Journal of Fish Biology, 1997)
Rainbow trout Oncorhynchus mykiss were exposed acutely to chloramine‐T at a therapeutic concentration (9mg l −1 ) under moderately hypoxic (water P o 2 : l00 mmHg) or hyperoxic (water P o 2 : 430mmHg) conditions and arterial blood gas tensions ( P ao 2 and P aco 2 ) and pH were monitored using an extracorporeal circulation. Hypoxia, alone, resulted in an increased ventilation frequency, a decrease in both arterial P co 2 and P o 2 and an increase in arterial pH. There was no effect of chloramine‐T exposure on the measured variables as compared with pre‐exposure (hypoxia baseline) values. Hyperoxia, alone, resulted in a decrease in ventilation frequency, an increase in arterial P co 2 and P o 2 , and a decrease in arterial pH. Chloramine‐T exposure under these conditions caused a significant increase in ventilation frequency, but no significant effect on arterial blood gases or pH as compared with the hyperoxia baseline values. Despite the increase in ventilation caused by chloramine‐T during hyperoxia, there was no reduction in P co 2 or increase in P o 2 . Although these results were of little pathological significance, this study suggests that chloramine‐T, although stimulating ventilation, was impairing the diffusion of co 2 across the gill probably by the secretion of branchial mucus and enhancing the gill boundary layer.

The effects of hypercapnia on branchial and renal calcium fluxes in the rainbow trout ( Oncorhynchus mykiss ) - W. M. MacKenzie; S. F. Perry (Journal of Comparative Physiology B, 1997)